A comparative study on pathological features of transgenic rat lines expressing either three or four repeat misfolded tau. Issue 11 (26th April 2018) - Valachova, Bernadeta; Brezovakova, Veronika; Bugos, Ondrej; Jadhav, Santosh; Smolek, Tomas; Novak, Petr; Zilka, Norbert
Abstract: Human tauopathies represent a heterogeneous group of neurodegenerative disorders characterized by distinct clinical features, typical histopathological structures, and defined ratio(s) of three‐repeat and four‐repeat tau isoforms within pathological aggregates. How the optional microtubule‐binding repeat of tau influences this differentiation of pathologies is understudied. We have previously generated and characterized transgenic rodent models expressing human truncated tau aa151–391 with either three (SHR24) or four microtubule‐binding repeats (SHR72). Here, we compare the behavioral and neuropathological hallmarks of these two transgenic lines using a battery of tests for sensorimotor, cognitive, and neurological functions over the age range of 3.5–15 months. Progression of sensorimotor and neurological deficits was similar in both transgenic lines; however, the lifespan of transgenic line SHR72 expressing truncated four‐repeat tau was markedly shorter than SHR24. Moreover, the expression of three or four‐repeat tau induced distinct neurofibrillary pathology in these lines. Transgenic lines displayed different distribution of tau pathology and different type of neurofibrillary tangles. Our results suggest that three‐ and four‐repeat isoforms of tau may display different modes of action in the diseased brain. Abstract : Using immunohistochemistry and proteomic analysis, we compare the pathological hallmarks of three and four repeats tauopathy in transgenic rat models. We show that the distribution of tau pathology and the type of neurofibrillary tangles are different in the three and four repeat tauopathies. This suggests that the three‐ and four repeat isoforms of tau may display different modes of action in the diseased brain.